Study of Esterification between Oleic Acid and 2-Ethyl Hexanol by using the Microwave Method - Hana Melyana Pertiwi Manurung; Juliati Br. Tarigan; Cut Fatimah Zuhra (International Journal of Ecophysiology, 2023)
Oleic acid is an unsaturated fatty acid, has a rancid odor and the main component of palm oil. To increase the value of oleic acid which has a C18 chain, it has the potential as a raw material for making long chain fatty acid esters. This fatty acid ester from vegetable oil is an emollient ester which is biodegradable which was synthesized with 2-ethyl hexanol using the Microwave method. In the last ten years, the microwave method has been widely used in organic synthesis. This esterification reaction was carried out using a modified home microwave by making a hole on top as a place for the ball cooler equipped with a stirrer, and using an acid catalyst. Characteristics of long chain fatty acid esters will be tested by FTIR and GC-MS. FTIR test results showed absorption of specific functional groups, while GC-MS was able to show the presence of long chain fatty acid ester compounds.